Functional Outcomes in Calcaneal Fracture Treated with Calcaneal Perimeter Plating - Hussain, Asad Moiz; Amin, Muhammad Suhail; Qureshi, Bilal Ahmad; Tareen, Najeeb Ullah (Pakistan Armed Forces Medical Journal, 2025)
Objective: to compare the Lateral Extensile Approach with the less invasive Sinus Tarsi Approach regarding functional outcomes and wound complications. Study Design: Quasi-experimental study.Place and Duration of Study: Department of Orthopaedic Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Dec 2023 to Nov 2024.Methodology: Forty-four patients with a closed, isolated calcaneal fracture with optimal skin condition were sequentially enrolled into two groups. All patients underwent open reduction internal fixation with the same calcaneal perimeter plate using the Lateral Extensile Approach in Group-A patients and the Sinus Tarsi Approach in Group-B patients. Clinical outcome was assessed by The American Orthopedic Foot and Ankle Society Score at 6 months. The adequacy of reduction was evaluated by Calcaneal Width, Bohler’s, and Gissane’s angle via post-operative radiograph. Patients were followed up at 2 weeks, 3, and 6 months for documentation of soft tissue complications.Results: Patients in both Groups demonstrated satisfactory reduction of fractures with no significant difference in Calcaneal Width, Bohler’s or Gissane’s angle. Similarly, no substantial variance was observed in the American Orthopedic Foot and Ankle Society score at 6-months follow-up. The lateral extensile Group had two superficial and one deep flap-related complication, while none was noted in the sinus tarsi Group.Conclusion: The current study suggests that the Sinus Tarsi Approach should be the preferred technique for treating DIACFs, as it produces similar results and fewer complications.